DETECTION AND GENOTYPE DETERMINATION OF LYMPHOCYSTIS DISEASE VIRUS FROM ORANGE CLOWNFISH Amphiprion percula IN BATAM - Murwantoko Murwantoko; Endang Wijayanti; Sri Agustatik; Harshelly Valianti; Lalla Kumala Yulanda; Nur Lailatul Firotun Nukmah (Indonesian Aquaculture Journal, 2022)
The orange clownfish, Amphiprion percula, is a popular fish in the global marine ornamental trade. In March 2021, several orange clown fish at Batam Mariculture Development Center exhibited lethargic behavior with wart-like nodules on the fins suggesting a viral disease infection. This study aimed to detect the suspected viral disease agent from the clownfish and determine its genotype based on the major capsid protein gene. The fish tissues with wart-like nodules were collected and fixed in 96% ethanol. The DNA was extracted from the tissues and used as the template for the amplification of the major capsid protein (MCP) and myristylated membrane protein (MMP) genes using polymerase chain reaction (PCR). The nucleotide sequences of the PCR products were analyzed for their homology using the Basic Local Alignment Search Tool (BLAST). Multiple alignments of the amino acid sequence of MCP were performed using MEGA-X to determine the genotype. The PCR amplification produced the expected bands for detecting MCP, MMP and DNAPol genes. These results indicated the presence of Lymphocystis disease virus (LCDV), designated as LCDV-Oc-Btm. The sequencing of MCP and MMP genes produced the 1221 and 407 nucleotides, respectively. The BLAST analysis showed the highest identity was obtained with the species of LCDV-1 (LCDV-Sa strain) at 91.04 % and 88.19 % for MCP and MMP, respectively. The UPGMA phylogenic tree showed LCDV-Oc-Btm differs from the existing genotype and can be assigned as a new genotype. This study concludes that LCDVOc-Btm is a novel species of lymphocystis disease virus.